Question #29fca

1 Answer
Nov 3, 2017

x=3 and y=-1

Explanation:

First, as there are 2 unknowns in the question, we can find the relationship bewteen the 2 unknowns, like x= ?

In this question,
x-y=4 .......... (1)
x^2-y^2=8 ..........(2)

From (1), we know that x=4+y.........(3)
Then, we can sub (3) into (2),
(4+y)^2-y^2 =8
4^2+2*4*y+y^2-y^2=8
16 +8y=8
8y=-8
y=-1

We get the value of y, but we still don't know x, so we can sub y=-1 into (3)
x=4+y=4+(-1)=4-1=3

Here we get x=3 and y=-1 and it's the answer. Hope this can help you :)